Anaphylactic reaction to polyethylene‐glycol conjugated‐asparaginase: Premedication and desensitization may not be sufficient. Issue 4 (5th August 2013) - Sahiner, Umit M.; Yavuz, S. Tolga; Gökce, Muge; Buyuktiryaki, Betul; Altan, Ilhan; Aytac, Selin; Tuncer, Murat; Tuncer, Ayfer; Sackesen, Cansin
Abstract: In hypersensitive reactions to native L‐asparaginase, either premedication and desensitization or substitution with polyethylene glycol conjugated asparaginase (PEG‐ASP) is preferred. Anaphylaxis with PEG‐ASP is rare. An 8‐year‐old girl and a 2.5‐year‐old boy, both diagnosed as having acute lymphoblastic leukemia, presented with native L‐asparaginase hypersensitivity and substitution with PEG‐ASP was preferred. They received a premedication (methylprednisolone, hydroxyzine and ranitidine) followed by desensitization with PEG‐ASP infusion. Both patients developed anaphylaxis with peg‐asparaginase. These are the first reported cases of anaphylactic reaction to PEG‐ASP, despite the application of both premedication and desensitization. Anaphylaxis with PEG‐ASP is very rare and premedication and desensitization protocols may not prevent these hypersensitive reactions.